2014
DOI: 10.17957/jgiass/2.2.511
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Osteoporosis in Relation to Serum Calcium and Phosphorus in Aging Women

Abstract: Osteoporosis is increasingly being recognized by the medical fraternity as a significant health problem. This research was designed to study the incidence of osteoporosis in post-menopausal women and its relation to body mass index, body muscles, body fat and mineral status (calcium and phosphorus). Thirty samples of post-menopausal women aging between 45-60 years were divided into 3 groups. Body weight and height seemed to be tested through the use of electronic weighing balance and Stadiometer. Body muscles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Indumati et al and Prabha et al found that osteoporotic patients had normal or low serum calcium. The increase in alkaline phosphatase levels in osteoporosis results from hormonal variations . In our osteoporotic patients, phosphorus and alkaline phosphatase levels were significantly higher which is in agreement with Gallagher et al and Prabha et al results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Indumati et al and Prabha et al found that osteoporotic patients had normal or low serum calcium. The increase in alkaline phosphatase levels in osteoporosis results from hormonal variations . In our osteoporotic patients, phosphorus and alkaline phosphatase levels were significantly higher which is in agreement with Gallagher et al and Prabha et al results.…”
Section: Discussionsupporting
confidence: 93%
“…In contrary to our results, Hedley et al detected a relation between age and gain of weight and explained this by the effect of increasing age on the decrease of metabolic rate inducing fat formation and deposition. Shakoor et al reported nonsignificant correlation between BMI and osteoporosis. Additionally, Asomaning et al detected that BMI and BMD were inversely correlated.…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with other studies observing that serum calcium levels are typically maintained between 8.5 and 10.5 mg/dl, which is a constrained range. Serum calcium concentrations, however, are just 0.1 to 0.2 percent of extracellular calcium, or just 1% of the total body calcium [19] Shakoor, Sadaf, et al (2014). As a result observed were high significant patients osteoporosis and control, serum calcium levels are a poor indicator of the total amount of calcium.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies showed a significant relationship; increasing serum phosphorus level and the subsequent increase in PTH level have destructive effects on bone mass. 59,60 Correlations (OR) analyses suggested that normal BMI, older age, longer dialysis duration, female gender, DM and low serum Vitamin D could be potentially stronger risk factors compared to the other factors studied. However logistic regression (backward) analysis revealed that age, dialysis duration and BMI remained significantly associated with bone mass status.…”
Section: Ipth and Bone Mass Statusmentioning
confidence: 99%